2022
DOI: 10.3390/laws11040056
|View full text |Cite
|
Sign up to set email alerts
|

Reforming the Law on Consent to Medical Treatment for Trans Youth: A Renewed Call for Legislative Intervention

Abstract: Australian trans youth seeking medical treatment for gender dysphoria can encounter significant legal barriers to healthcare. Legal requirements for obtaining valid consent to gender-affirming care, first established in 2004, mean that an application to the Family Court is required in many cases before treatment can be provided. The development of Australian law concerning consent for the medical treatment of trans youth has been slow, haphazard, and remains incomplete. The Family Court process has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Adolescents' participation in society is essential to ensure just treatment of this important social group (Patton et al 2016(Patton et al , 2018Sawyer et al 2012). As shown by many of the articles in this Special Issue, ensuring greater participation by children and adolescents is essential for best practice and good outcomes in a range of settings spanning child care and protection decision-making (Cashmore et al 2023); medical decision-making (Jowett et al 2022); and forensic interviewing in child sexual abuse investigations (Holder et al 2023). Enhanced participation also boosts civic engagement, and will enhance social policy, and ensure pressing social issues are more fully understood and can be remediated by appropriate social policy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adolescents' participation in society is essential to ensure just treatment of this important social group (Patton et al 2016(Patton et al , 2018Sawyer et al 2012). As shown by many of the articles in this Special Issue, ensuring greater participation by children and adolescents is essential for best practice and good outcomes in a range of settings spanning child care and protection decision-making (Cashmore et al 2023); medical decision-making (Jowett et al 2022); and forensic interviewing in child sexual abuse investigations (Holder et al 2023). Enhanced participation also boosts civic engagement, and will enhance social policy, and ensure pressing social issues are more fully understood and can be remediated by appropriate social policy.…”
Section: Discussionmentioning
confidence: 99%
“…When legislation is absent, and the law is unclear about the parameters of children's capacity for decision-making, a court response becomes necessary. In this Special Issue, the analysis by Jowett et al (2022) emphasized the harms which a court intervention in decisions about consent to gender-affirming medical treatment can cause for trans youth, including health, wellbeing and financial implications. Jowett et al (2022) identified the widespread concern about these matters shared amongst the legal fraternity, judicial officers and health practitioners.…”
Section: The Evolving Legal Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…However, the relative scarcity of specialist gender services and practitioners with experience providing affirmative care to trans people constitutes a barrier to service access for both trans adults and young people (Riggs et al., 2014 ; Strauss et al., 2021 ). In Australia, consent of both parents is needed prior to commencement of any gender-affirming medical treatment, even when a young person is assessed as competent to consent, leading many families to navigate the Family Court system and creating additional barriers to care (Jowett et al., 2022 ). Both globally and within Australia, trans young people report difficulties in accessing services appropriate to their needs (Chong et al., 2021 ; Winter et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%